Analysis Of The Effect Of The Rupiah Exchange, World Oil Price, World Gold Price On The Joint Stock Price Index In The Indonesia Stock Exchange - Rohmawati, Suniti; Munasirotul Mutmainnah; Fitria Asas; Ulfatul Khasanah (International Journal of Science, Technology & Management, 2022)
Stock price fluctuations that could be traded on the stock exchange can be seen from JCI Indonesia so that we can know whether the market is bullish (strong) or bearish (weak). All in result by 2 factors, internal factors and eksternal. Many theory of past research revealed that the composite stock price index is influenced by several factors. Three factors including the value of the rupiah, world gold prices, and world oil prices. Because other than gold commodity rupiah exchange rate and the oil will affect the movement of stock indices on the StockExchange. The study population was the entire data rupiah exchange rate, oil prices and gold prices on the world in 2011-2014 and since such data exist today (historical price). This study uses statistical analisisis, Multiple linear regression, and the F test and T and test (coefficient of determination (R2)), Normality Test, Test Heteroskidastity. Based on hypothesis testing shows that world oil prices and world gold prices have a negative effect and no significant effect on the JCI while the rupiah / US $has a positive and significant impact on JCI.